Digital Navigation: The Role of Marketing Literacy, Employee Engagement, and Internal Culture in SMEs' Success - Kaniawati, Keni; Rahmani, Shinta; Ariawan, Ariawan; Fadhlan, Abdi; Ahmad, Abdul Kadir (Jurnal Aplikasi Manajemen, 2024)
Digital marketing is essential for SMEs to achieve and maintain a competitive advantage. This study investigates the influence of digital marketing literacy and employee engagement in digital marketing campaigns on marketing performance, with internal marketing culture, government policy, and market competitiveness as moderating factors. The research uses a quantitative survey method, targeting SMEs in West Java active in digital marketing. Purposive sampling yielded 240 respondents. Data were collected via questionnaires and analyzed using Smart PLS 3 to test the relationships in the conceptual model. Results indicate that digital marketing literacy does not significantly impact marketing performance. However, employee engagement in digital marketing campaigns positively and significantly affects marketing performance. Internal marketing culture enhances the impact of digital marketing literacy and employee engagement on marketing performance. Government policy and market competitiveness do not significantly moderate the effect of digital marketing literacy on marketing performance, but market competitiveness does moderate the impact of employee engagement on marketing performance. This study uncovers new insights about how digital marketing works in SMEs and concludes by recognizing the crucial influence of employee involvement on enhancing marketing performance. This can be a significant advantage in SMEs; visibility and competitiveness are points to always consider, and involving employees in digital marketing efforts is one of them.